Amerykańska wizja pokoju na Bliskim Wschodzie. Od „małych kroków” Henry’ego Kissingera do mediacji Jimmy’ego Cartera - Lorenc, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
An American model of peace in the Middle East, which evolved from Kissinger’s ‘little steps’ to the separatist agreements of Camp David, was to serve the purpose of regulating the Arab-Israeli conflict and strengthening Washington’s influence. In the address delivered on January 23, 1980 (that provided the foundation for the so called ‘J. Carter doctrine’) the US President said that every “attempt by any outside force to gain control of the Persian Gulf region will be regarded as an assault on the vital interests of the United States of America” and thus it “will be repelled by any means necessary, including military force”. The abandonment of the Nasserian tradition did not help A. Sadat to win supporters in internal matters. The protest of Nasserists and the Association of Muslim Brothers against the reconciliation with Israel resulted in a tragic attack against the Egyptian president. A. Sadat’s death on October 6, 1981 was a blow for the advocates of the peace process. Whether to continue the separatist policy towards Israel or not was up to the will of the new political authorities in Egypt.